Perception of Russian Politics in Galicia in Diaries and Memoirs of World War I Participants - Yu. A. Zherdeva; E. I. Sumburova; M. V. Cherkasova (Научный диалог)
The problem of perception of Russian politics in Galicia during the First World War by participants in military operations is considered. The relevance of the study is due to the interest of modern society in historical sources of personal origin. The novelty is determined by a wide corpus of diaries and memoirs of participants in hostilities, un-published archival ego-documents introduced into scientific circulation. Based on new sources, the actions of the Russian authorities and the army in Galicia in 1914—1916 are interpreted. Plots are revealed that are not recorded by officials in official documents. Unjustified decisions of the local administration, bureaucratic confusion and arbitrariness are analyzed. The degree of influence of official Russian propaganda on the position of combatants and Galicians is determined in the study. Different points of view among Russian society on the organization of governance in Galicia and the national and confessional policy pursued there are revealed. The diaries and memoirs of the combatants made it possible to look at the events that took place in Galicia from the perspective of an eyewitness, shedding light on the features of everyday life, both of the local civilian population, and of military units, and of the medical service who found themselves in the conquered territories.